Jornal da jacy: tecnologia social para promoção de saúde e cidadania no sistema prisional. - Santos, Amasília Romeiro dos (2025)
There are a series of laws and policies, such as the National Policy for Comprehensive Health Care for People Deprived of Liberty in the Prison System (PNAISP), which guarantee this population's right to health and access to the Unified Health System (SUS). However, the Brazilian prison system presents immense challenges in implementing actions to promote, prevent and reduce harm due to prejudices and the punitive logic prevalent in this context. In this unique territory, the Prison Primary Care Team “Beyond the Bars” developed Jornal da Jacy, a printed newspaper aimed at people deprived of their liberty. This is a social technology that aims, through access to information, to promote health and citizenship. The proposal considered specificities of the prison community, which is characterized by isolation and various restrictions. To achieve the proposed objective, an editorial team was created to define the agenda, survey events and issues relevant to publication and layout of the newspaper. The newspaper is distributed monthly with one copy per cell, among 1,900 people deprived of their liberty. The proposal is pioneering and innovative as it considers communication and access to information as part of the health production process. In a context of extreme vulnerability, such as prison, proposing strategies and using social technologies such as Jornal da Jacy, which implement the principles and guidelines of the SUS, guarantees a better quality of life and dignity for people who are deprived of their liberty